(untitled) (Filologia e Linguística Portuguesa, 2014)
In this work, a known incompatibility between the Linear Correspondence Axiom (cf. Kayne, 1994) and bare phrase structure (cf. Chomsky, 1995a) is presented and some of the main proposals for solving it are surveyed and discussed. This survey is part of an ongoing investigation which aims to provide an alternative solution. Except for Hornstein’s (2009) proposal, I argue that all other solutions are unsatisfactory from a minimalist perspective and that an adequate solution to this problem demands some reconception of syntax, at least with regard to the fundamental structure building operation, Merge, in such a way that asymmetry is obtained (and not lost) since the beginning of the derivation. Therefore, the structure would not have to be “saved” in the course of derivation, and syntax would have an essentially asymmetric character, a stronger result than that of Kayne (1994), which claimed for an “antisymmetric” character of syntax.